Lower limb maltorsion and acetabular deformity in children and adolescents with X-linked hypophosphatemia - Stauffer, Alexandra; Raimann, Adalbert; Penzkofer, Stefan; Ganger, Rudolf; Radler, Christof; Mindler, Gabriel T. (Frontiers in Endocrinology, 2024)
1) Background: X-linked hypophosphatemia (XLH) is a rare monogenetic skeletal disorder. Lower limb deformities contribute substantially to impaired gait quality and burden of disease in patients with XLH.Standardized data regarding onset and severity of lower limb maltorsion are unavailable. This study aimed to evaluate lower limb maltorsion using rotational magnetic resonance imaging (MRI) and computed tomography (CT). ( 2) Methods: Rotational MRI and CT of children and adolescents with verified XLH were evaluated retrospectively. Femoral and tibial torsion, acetabular anteversion, and axial acetabular coverage were measured and compared with published age-adapted radiographic, clinical measurements and MRI data, respectively. (3) Results: Fifteen patients (mean age, 10.7 years) were included in the study. Decreased femoral torsion was observed in 47% (14/30 femora) and femoral retrotorsion in 17% (5/30 femora). Ten of 13 hips with coxa vara deformity presented with decreased femoral antetorsion. Reduced external tibial torsion manifested in 64% (18/28 tibiae). Abnormal axial femoral head coverage was present in 67% (20/30 hips), whereas 53% (16/30 hips) showed increased acetabular anteversion. (4) Conclusion: Femoral and tibial torsional pathologies were found in children and adolescents with XLH. The occurrence of severe femoral retrotorsion in a 2-year-old child prior to ambulation raises questions regarding the biomechanical impact of gait on the development of torsional deformities in XLH.